Fast sign-detection algorithm for residue number system moduli set {2n − 1, 2n, 2n+1 − 1} - Niras, Cheeckottu Vayalil; Kong, Yinan (Chronic diseases and translational medicine, 2016)
Sign detection is an essential part of many computer hardware designs, and is not a trivial task in residue number systems because it is a function of all the residues. This study proposes an algorithm for the residue number system with a three-moduli set {2n − 1, 2n, 2n+1 − 1} using New Chinese Remainder Theorem II. The unit is built with one n-bit carry-save adder and a 2n-bit parallel prefix carry-generation unit. In the best case the Synoposys 90 nm synthesis result shows a 24% reduction in the area–delay product than existing algorithms for the same moduli set.